Analysis of Patient Satisfaction with Health Services in Ambacang Padang Health Center Based on Electronic - Derry Trisna Wahyuni S; Hilda Harun; Agnes Ratna Saputri; Khaeriah B; Wibowo Hanafi Ari Susanto (Miracle Journal Get Press, 2025)
Quality health services and satisfying patients are the main factors in increasing trust and effectiveness of services at puskesmas. The implementation of electronic-based service system is expected to improve the quality of Service and patient satisfaction. Objective: This study aims to analyze the level of patient satisfaction with electronic-based health services in Ambacang Padang Health Center. Methods: this study uses a quantitative approach with descriptive survey design. Data were collected through questionnaires distributed to 150 patients who had used electronic services at the Ambacang Health Center. Data analysis was conducted using descriptive statistics and regression analysis to determine the effect of Service variables on patient satisfaction. Results: the results showed that patients were satisfied with electronic-based services at the Ambacang Padang Health Center with an average satisfaction score of 4.1 on a scale of 5. The main factors contributing to patient satisfaction include ease of access to services, speed of Service, and quality of communication between health workers and patients. Implication: This finding gives an idea that the implementation of electronic service system is able to improve the quality of health services in puskesmas, so that it can be used as a reference for further service development, both in terms of technology and human resources. Conclusion: electronic-based health services in Ambacang Padang Health Center are effective in increasing patient satisfaction. Therefore, it is necessary to make continuous improvements to the system and training of officers so that the quality of service can be maintained and improved.